Pipelines 2019. proceedings of sessions of the Pipelines 2019 Conference, July 21-24, 2019, Nashville, Tennessee - Heidrick, Jeffrey W.; Mihm, Mark S. (American Society of Civil Engineers, 2019)
This collection contains 75 peer-reviewed papers on condition assessment, construction and rehabilitation of pipelines. Topics include: condition assessment and trenchless rehabilitation; construction case studies; corrosion control; and tunneling and horizontal directional drilling. This collection will be of interest to utility and pipeline owners, design and consulting engineers, contractors, manufacturers, suppliers, researchers, and pipeline professionals.